THE INFLUENCE OF MARMET TECHNIQUE ON ASI PRODUCTION IN POST PARTUM MOTHERS - Putri, Vivi Dwi Putri; Wika Sepiwiryanti; Adhika Wijayanti (LPPM STIKES Al-Ma'arif Baturaja, 2024)
Breast milk is the best and most ideal food for babies, because breast milk contains all the nutrients needed in the right amount and balance. In addition, breast milk contains immune substances or antibodies that function to protect infants from various germs so that they can prevent various diseases that are at risk of increASIng morbidity and mortality in infants. However, until now there are still many babies who do not get breast milk on the first day of birth, this causes many nutritional problems for babies in Indonesia to occur, one of which is insufficient nutrition in infants. This research is a quantitative method using a quASI-experimental method. This study aims to determine whether there is an effect of the Marmet Technique on Breast Milk Production in Postpartum Mothers at the Village Health Post of Simpang Bayat Bayung Lencir in 2023. This research was conducted in March-June 2023. The population in this study were all post partum mothers 1-7 days at the Simpang Bayat Poskesdes totaling 24 post partum mothers. The sample of this research is 20 people. The technique used is Accidental Sampling. This research uses univariate and bivariate analysis. Based on the results of the study, it was shown that there was an increase in milk production using the guinea pig technique and data analysis obtained p value = 0.000 (α < 0.05) so that there was an influence between the guinea pig technique and breast milk production. It is hoped that the results of this study can provide additional knowledge for health workers in providing care for breastfeeding mothers in increASIng breast milk production, as well as for midwifery education can add to midwifery literature so that they can provide broader insights on maternity, especially regarding how to expel breast milk